Simultaneous determination of selected herbicides in dam lake, river and well water samples by gas chromatography mass spectrometry after vortex assisted binary solvent liquid phase microextraction - Bodur, Suleyman; Balurdere, Emine Gulhan (ELSEVIER, 2019)
A sensitive and accurate binary solvent-liquid phase microextraction (BS-LPME) method was developed for the determination of alachlor, nitrofen and bifenox as herbicides in environmental water matrices at trace levels by gas chromatography mass spectrometry (GC-MS). The binary solvent system was used to improve the extraction efficiencies of all analytes in comparison to the single extraction solvents. A comprehensive univariate optimization was performed to determine optimum experimental conditions based on the type and amount of extraction and dispersive solvents, and mixing period. The optimum parameters obtained were binary solvent (100 mu L dichloromethane + 100 mu L 1,2-dichloroethane), 2.5 mL ethanol and 15 s of mixing by vortex. Under the optimum conditions, satisfactory analytical figures of merit were calculated for the analytes. The limits of detection (LODs) obtained for alachlor, nitrofen and bifenox were 0.30, 0.60 and 2.0 ng mL(-1), respectively. Spiked recovery experiments were carried out on dam lake, river and well water samples and the percent recoveries calculated fell within the range of 83-121%.
Keywords: Pesticide; DLLME; GC-MS; Alachlor; Nitrofen; Bifenox; TRIAZINE HERBICIDES; RESIDUE ANALYSIS; AQUEOUS SAMPLES; EXTRACTION; PESTICIDES; SOLIDIFICATION; METABOLITES; CADMIUM; JUICE; Chemistry